Remifentanil vs. Lidocaine on Response to Tracheal Tube during Emergence of General Anesthesia - Kambiz Sadegi; Daryoush Rostami; Mania Kaveh (Journal of Cardio-Thoracic Medicine, 2014)
Introduction: Response to tracheal tube during emergence of general anesthesia is a main concern. We aimed to compare the effect of Remifentanil and Lidocaine on response to tracheal tube during emergence of general anesthesia. Materials and Methods: In this randomized clinical trial, we enrolled 80 consecutive patients with American Society of Anesthesiology (ASA) physical status I–II, who underwent general anesthesia for general surgery in Amir-Al-Momenin Hospital on Zabol University of medical sciences from May 2011 to September 2011. Patients received either i.v. lidocaine 1.5 mg /kg (Group L) or 0.5mic/kg/min of Remifentanil (Group R) for emergence from anesthesia. Results: The frequency of cough during emergence from general anesthesia was significantly higher in Group L than in Group R (70.7% vs. 40.3%, P=0.014). Also the grade of cough during the emergence was significantly higher in Group L than in Group R (P=0.013).The difference between two groups regarding sedation level, visual analogue scale (VAS), and pethidine consumption were not significant (P=0.08). Conclusion: we specified Remifentanil reduces cough during the emergence from general anesthesia more effective than Lidocaine in patients undergoing general surgery. In addition, Remifentanil and i.v. lidocaine revealed comparable impact regarding VAS scoring, sedation level and pethidine consumption.